PHARMACOGENETIC STUDIES IN CARDIOLOGY: THE PROBLEM OF "DEPTH" OF THE ISSUE STUDY AND THE CORRECTNESS OF USING "GENETIC" TERMS - D. A. Sychev; G. I. Lifshits (Рациональная фармакотерапия в кардиологии, 2018)
.